Pengaruh Gaya Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening(Studi Kasus Bank Mandiri Divisi Commercial Banking Kota Banjarmasin) - Auliana; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
This study aims to examine the effect of Transformational Leadership Style and Organizational Culture on Employee Performance with Motivation as an Intervening Variable (Case Study of Bank Mandiri Commercial Banking Division, Banjarmasin City). The approach used in this research is quantitative, with the type of causality associative research. The sampling method used nonprobability sampling with saturated sampling method for 32 employees of KC. Bank Mandiri Banjarmasin in the Commercial Banking division. Data collection using a google form questionnaire was distributed via Whatsapp to each respondent. Data analysis using SmartPLS software. The results showed that transformational leadership style had a significant effect on the performance of Bank Mandiri KC Lambung Mangkurat employees in the Commercial Banking division, Organizational culture had a significant effect on the performance of Bank Mandiri KC Lambung Mangkurat employees in the Commercial Banking division, and the transformational leadership style had a significant effect on work motivation at Bank Mandiri KC Lambung Mangkurat. Commercial Banking division, Organizational culture has a significant effect on work motivation of Bank Mandiri KC Lambung Mangkurat Commercial Banking division, Transformational leadership style has a significant effect on organizational culture of Bank Mandiri KC Lambung Mangkurat Commercial Banking division, Work motivation has a significant effect on employee performance at Bank Mandiri KC Lambung Mangkurat division Commercial Banking, Transformational leadership style has a significant effect on employee performance through employee motivation at Bank Mandiri KC Lambung Mangkurat div Commercial Banking content, and organizational culture have a significant effect on employee performance through employee motivation at Bank Mandiri KC Lambung Mangkurat Commercial Banking division